Experimental Studies on the Conical Cap tray Performance - Taleb Zarei; Jamshid Khorshidi; Rahbar Rahimi; Ali Zarei (Journal of Chemical and Petroleum Engineering, 2017)
In the present study, experimental investigations about the hydrodynamics of the conical cap tray (ConCap tray) have been carried out. The ConCap tray is an innovative and novel type of cap trays. The effect of the different weir height (2.5, 5 and 7 cm) on the weeping, entrainment and the total pressure drop for the ConCap tray was measured, compared and correlated. The hydraulic experiments were carried out in an industrial scale simulator rig with an inner diameter of 1.2 m which has two test trays (ConCap tray) and two chimney trays. It was found that the weir height affects only on the pressure drop. The recommended weir height for the ConCap tray must be 2.5 cm because of observed spray flow regime on the tray and experimental results in different weir height which shows no effect on the weeping and entrainment rates. Moreover, the hydraulic behavior of the tray in the lower operating limits was also investigated.